Overview of randomized trials of intravenous heparin in patients with acute myocardial infarction treated with thrombolytic therapy. - Mahaffey, K; Granger, C; Collins, R; O'Connor, C; Ohman, E; Bleich, S; Col, J; Califf, R (1996)
Intravenous heparin is routinely given after thrombolytic therapy for patients with acute myocardial infarction in the United States and in some, but by no means all, other countries. Several trials have documented improved infarct-artery patency in patients treated with heparin; however, none was large enough individually to assess the effect of heparin on clinical outcomes. We performed a systematic overview of the 6 randomized controlled trials (1,735 patients) to summarize the available data concerning the risks and benefits of intravenous heparin versus no heparin after thrombolytic therapy. Mortality before hospital discharge was 5.1% for patients allocated to intravenous heparin compared with 5.6% for controls (relative risk reduction of 9%, odds ratio 0.91, 95% confidence interval 0.59 to 1.39). Similar rates of recurrent ischemia and reinfarction were observed among those allocated to heparin therapy or control. The rates of total stroke, intracranial hemorrhage, and severe bleeding were similar in patients allocated to heparin; however, the risk of any severity of bleeding was significantly higher (22.7% vs 16.2%; odds ratio 1.55, 95% confidence interval 1.21 to 1.98). There was no significant difference in the observed effects of heparin between patients receiving tissue-type plasminogen activator and those receiving streptokinase or anisoylated plasminogen streptokinase activator complex, or between patients who did and did not receive aspirin. The findings of this overview demonstrate that insufficient clinical outcome data are available to support or to refute the routine use of intravenous heparin therapy after thrombolysis. It is not known if these findings are due to lack of statistical power, inappropriate levels of anticoagulation, or lack of benefit of intravenous heparin. Large randomized studies of heparin (and of new antithrombotic regimens) are needed to establish the role of such therapy.